Standardization of growing medium composition for pot plant production of African marigold (Tagetes erecta L .) var ‘Double Orange’ - SANKAR, MINI; U, Sreelatha; P, Prameela; Gopal, Niranjana; Paul, Reshmi (Journal of Tropical Agriculture, 2024)
Standardization of suitable growing medium composition for pot plant production of African marigold (Tagetes erecta L.) variety Double Orange was carried out at the Department of Floriculture and Landscaping, College of Agriculture,Vellanikkara, Kerala, India during 2020-21. Five growing media viz.,M1: cocopeat (60%) + vermicompost (20%) + vermiculite (10 %) + rice husk (10%), M2: cocopeat (60%) + FYM (20%) + vermiculite (10%) + rice husk (10%), M3: cocopeat (40%) + soil (20%) +vermicompost (20%) + vermiculite (10%) + rice husk (10%), M4: cocopeat (40%) + soil (20%) +FYM (20%) + vermiculite (10%) + rice husk (10%) and M5: soil: FYM: sand (1:1:1) were tested to assess the suitability for pot plant production of marigold. Experiment was laidout in completely randomized block design. Parameters such as plant spread (cm), number of branches per plant, number of leaves per branch, number of flowers per plant, flower diameter, flowering duration and field life of individual flowers which decide the attractiveness of the potted African marigold were observed. Medium (M4) consisting of cocopeat (40%) + soil (20%) +FYM(20%) + vermiculite (10%) + rice husk (10%) was found to satisfy all these criteria. Hence Medium (M4) can be recommended as a suitable growing medium for production of compact potted African marigold plants.